Writing Development in the L2: A Look into Depth of Processing Using Verbal Protocols - Adrada-Rafael, Sergio; Meschi, Rose (International Journal of Linguistics and Translation Studies, 2025)
Depth of processing (DOP) refers to the way information is processed in the mind and how it affects recall. Studies have examined DOP in different areas of L2, such as reading, and more recently attention has been paid to learners’ writing, but it remains to be more thoroughly studied. Therefore, to better understand the role of DOP in the incorporation of corrective feedback on the writings of English as a Foreign Language (EFL) language learners, and to find out how DOP is related to changes in the learners’ final written product, the present study asked 30 intermediate EFL learners having Persian as their L1 to edit their writings based on the feedback they received, either thinking aloud or being silent. Findings suggested that learners processed lexical items at a deeper level than grammatical items. A significant difference was found when comparing the quality of the two writing versions. Thinking aloud did not impact learners’ performance when compared to the silent condition. These findings contribute to the strand of recent studies that have looked into the role of DOP in L2 writing and highlight how DOP contributes to L2 learners’ writing development.